Masalah Komitmen Tempat Kerja: Fokus pada HRM dan Komitmen Organisasi - Santoso, Toto; Bastian, Adolf; Syahsudarmi, Siti (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The research was conducted at the Office of the Ministry of Religious Affairs in Siak with the aim of examining the role of job crafting in mediating the effect of human resource management practices on organizational commitment. The research population consisted of 177 individuals. Based on this population size, according to the Krejcie and Morgan table (1970), the sample size for this study was determined to be 123 individuals. The sampling method used in this study was Systematic Random Sampling. All respondents were utilized to obtain primary data related to the variables, which were collected through a questionnaire using a 5-point Likert scale. All data obtained were analyzed using Structural Equation Modeling (SEM) with the analytical tool Smart PLS 3.0. The study found that human resource management practices have a significant positive effect on organizational commitment; human resource management practices have a significant positive effect on job crafting; job crafting has a significant positive effect on organizational commitment; and job crafting mediates the effect of human resource management practices on organizational commitment.